2017
DOI: 10.1186/s40248-017-0107-2
|View full text |Cite
|
Sign up to set email alerts
|

Second lung malignancy and Richter syndrome in chronic lymphocytic leukemia: case report and literature review

Abstract: BackgroundChronic lymphocytic leukemia (CLL) is the most frequent lymphoproliferative disease. Transformation into Richter disease and occurrence of second malignancies involving the lungs are rare complications. The hallmarks of any thoracic involvement are still unknown.Case presentationWe report a case of a 56-year-old male patient, with history of tobacco smoking, who presented with recurrent hemoptysis, fatigue and weight loss. Physical examination was normal except a slightly enlarged supraclavicular lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A comprehensive literature review showed various malignancies coexisting with CLL/SLL [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. For example, CLL/SLL has been reported coincidentally with adenocarcinoma of the stomach, kidney, breast, colon, liver, and lung [ 3 , 10 , 11 , 12 ]. Based on our knowledge, this is the first study reporting the coexistence of endometrioid-type G2 endometrial cancer with CLL/SLL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive literature review showed various malignancies coexisting with CLL/SLL [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. For example, CLL/SLL has been reported coincidentally with adenocarcinoma of the stomach, kidney, breast, colon, liver, and lung [ 3 , 10 , 11 , 12 ]. Based on our knowledge, this is the first study reporting the coexistence of endometrioid-type G2 endometrial cancer with CLL/SLL.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an increased risk for the coexistence of a second malignancy, of epithelial and mesenchymal origin, has been reported in patients with CLL/SLL, for example, in lung cancer [ 3 ] or bladder and prostate cancers [ 4 ]. The development of a second malignancy was comparable in patients without or with chemotherapy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The VN has been well-established as a signal node for the spread of gastric cancer 4 - 9. In addition, the VN has been identified as a seeding location for cancers arising from myriad locations apart from the stomach, including the intestines,7 urogenital system,10 - 18 esophagus,19 common bile duct,20 liver,21 - 23 as well as the pancreas,24 , 25 and lungs 26. The VN has also been reported with squamous cell carcinoma and lymphoma 16 , 27 , 28.…”
Section: Introductionmentioning
confidence: 99%